1998
DOI: 10.1086/515592
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Normal Human Renal Tubular Epithelial Cells by Escherichia coli Shiga Toxins 1 and 2

Abstract: The cytotoxicity of Shiga toxin (Stx) 1 and Stx2 produced by Escherichia coli to human renal cortical epithelial cells (HRCEC) in primary culture was investigated. HRCEC express CD24, the marker of renal distal tubules, as well as globotriaosyl ceramide/CD77, the receptor for Stxs. Binding of Stxs to HRCEC was confirmed by positive staining with specific antibodies to Stxs. Treatment of HRCEC with Stxs induced rapid cell death, which was reversed in the presence of neutralizing antibody specific for Stx. DNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 48 publications
4
81
0
Order By: Relevance
“…Globotriaosyl ceramide (Gal␣(1-4)-Gal␀(1-4)-Glc␀1-ceramide) is differentially organized in glycolipid-enriched microdomains in mammalian membranes (44). After internalization of the holotoxin by receptor-mediated endocytosis, verotoxin inhibits protein synthesis resulting in necrosis and/or apoptosis (45)(46)(47). Whether RsAFP2-induced fungal growth arrest is a result of the induced membrane permeabilization or results from its interaction with a putative intracellular target is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…Globotriaosyl ceramide (Gal␣(1-4)-Gal␀(1-4)-Glc␀1-ceramide) is differentially organized in glycolipid-enriched microdomains in mammalian membranes (44). After internalization of the holotoxin by receptor-mediated endocytosis, verotoxin inhibits protein synthesis resulting in necrosis and/or apoptosis (45)(46)(47). Whether RsAFP2-induced fungal growth arrest is a result of the induced membrane permeabilization or results from its interaction with a putative intracellular target is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…For example, renal tubular epithelial cells express Gb3, which can bind Stx1 and 2 (Boyd and Lingwood, 1989;Kiyokawa et al, 1998;Taguchi et al, 1998;Uchida et al, 1999). In vitro experiments have revealed that Stx1 induces cell death in renal tubular epithelial cells through protein synthesis inhibition and apoptosis (Karpman et al, 1998;Kiyokawa et al, 1998;Taguchi et al, 1998;Williams et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The Shiga toxin receptor, globotriaosylceramide (Gb3), is a neutral glycosphingolipid that was first identified as an Ag of Burkitt's lymphoma and other tumors (54,55). Some human epithelial and endothelial cells and a subset of B lymphocytes located in germinal centers express Gb3 (55)(56)(57), while most other cell types are Gb3 negative. We have also demonstrated in mice that spleen and bone marrow cells do not express significant levels of Gb3.…”
Section: Discussionmentioning
confidence: 99%